THE INFLUENCE OF LAND REFORM ON TRANSFORMATION OF AGRICULTURAL LAND USE IN THE POLTAVA REGION - Kolesnyk, G. M. (Land Management, Cadastre and Land Monitoring, 2013)
In this article transformational changes in agricultural land use in Poltava region during the land reform were analyzed. The researchers determined the changes in the structure of land, agricultural goods produced by different farms and characterized the implementation of measures to protect the land.